Penerapan Metode Sorogan Pada Proses Penilaian Membaca Kitab Kuning Di Pondok Pesantren Putri Al Fathimiyyah Bahrul Ulum Tambak Beras Jombang - Putri, Sanya Novelisa; Nusantara, Widya (J+PLUS UNESA, 2024)
This research aims to describe and analyze the application of the sorogan method in the process of reading the yellowclassicalassessment process of reading the yellowclassical books at Al Fathimiyyah Bahrul Ulum Islamic Boarding School. Tambak Beras Jombang.. The approach used in the research is descriptive qualitative. The research was conducted using data collection techniques through the process of interviews, observation and documentation. Researchers used data analysis using data collection, data reduction, data presentation, and finally conclusion drawing and verification. The result of this research is that the sorogan method provides a comprehensive and effective approach in learning assessment. The application of the sorogan method in the process of assessing the yellowclassical books at Al Fathimiyyah Islamic Boarding School by means of educators conducting observations and interviews with students through the sorogan method. At Al Fathimiyyah Islamic Boarding School, there are two types of assessments used to measure students' understanding of the material that has been taught. The two types of assessment are written exams and oral exams using the sorogan method. sorogan creates a learning environment that encourages students to be active, critical, and reflective of the material being studied. The assessment of grade promotion using the sorogan method is carried out by requiring students to attend sorogan according to a certain schedule and in front of educators who have been determined for each class. educators assess students' performance based on several criteria, such as: accuracy of reading, understanding of material, ability to explain, and ability to think critically.